2018
DOI: 10.3389/fmicb.2018.00102
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Rare and Abundant Prokaryotic Phylotypes in the Prony Hydrothermal Field and Comparison with Other Serpentinite-Hosted Ecosystems

Abstract: The Bay of Prony, South of New Caledonia, represents a unique serpentinite-hosted hydrothermal field due to its coastal situation. It harbors both submarine and intertidal active sites, discharging hydrogen- and methane-rich alkaline fluids of low salinity and mild temperature through porous carbonate edifices. In this study, we have extensively investigated the bacterial and archaeal communities inhabiting the hydrothermal chimneys from one intertidal and three submarine sites by 16S rRNA gene amplicon sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 69 publications
(135 reference statements)
0
31
0
Order By: Relevance
“…Chimera sequences were identified and removed using vsearch (v2.3.4). The clustering to Operational Taxonomic Units (OTUs) (>97%) and their quality filtration were carried out using QIIME 1.9.1 (Caporaso et al, 2010) as described in (Frouin et al, 2018). Taxonomic assignment of the filtered OTUs was performed using the Uclust method against the SILVA database release for QIIME (v.123).…”
Section: Methodsmentioning
confidence: 99%
“…Chimera sequences were identified and removed using vsearch (v2.3.4). The clustering to Operational Taxonomic Units (OTUs) (>97%) and their quality filtration were carried out using QIIME 1.9.1 (Caporaso et al, 2010) as described in (Frouin et al, 2018). Taxonomic assignment of the filtered OTUs was performed using the Uclust method against the SILVA database release for QIIME (v.123).…”
Section: Methodsmentioning
confidence: 99%
“…Recent biogeochemical studies show that formate oxidation, likely carried out by sulfate reducing bacteria, supports the base of the LCHF ecosystem (Lang et al, 2018). At the Prony Hydrothermal Field in New Caledonia, a hybrid between marine and terrestrial serpentinites, sulfur-cycling organisms similar to the strictly anaerobic Dethiobacter alkaliphilus were identified that can utilize acetate and sugars with elemental sulfur, polysulfides and thiosulfate, yet cannot reduce sulfate directly (Sorokin et al, 2008;Pisapia et al, 2017;Frouin et al, 2018). For comparison, freshwater sites such as the Santa Elena ophiolite in Costa Rica and The Cedars in California lack sulfate (i.e., < 5.0 μM) and to date show little evidence of sulfur cycling (Crespo-Medina et al, 2017).…”
Section: Potential For Serpentinizing Ophiolites To Preserve Aspectsmentioning
confidence: 99%
“…Despite differences in the composition of microbial communities retrieved at PBHF compared to LCHF, PBHF chimneys interestingly harbor Archaea related to LCMS and to another Methanosarcinales phylotype (The Cedars Methanosarcinales, TCMS) [15], identified in springs of The Cedars ophiolite (California, USA [19]). The dominant Bacteria in PBHF relate to anaerobic Firmicutes and aerobic or facultative anaerobic Chloroflexi, Proteobacteria, and Bipolaricaulota (formerly Acetothermia) [13][14][15][16]. The co-occurrence of aerobic and anaerobic metabolisms at both LCHF and PBHF has been attributed to variable influences of the hydrothermal discharge creating anoxic environments within chimneys and of oxidized seawater intrusions from outside the chimneys [12,15].…”
Section: Introductionmentioning
confidence: 97%
“…Microbial communities sustained by serpentinization have recently been explored using next-generation sequencing and '-omic' technologies, although oceanic hydrothermal systems remain poorly explored compared to terrestrial springs due to difficulties in discovering and sampling sites at great water depth. Microbial taxa inhabiting LCHF chimneys differ from other serpentinite-hosted ecosystems [10][11][12], and even from PBHF [13][14][15][16]. Nevertheless, LCHF shares some microbiological commonalities with these other serpentinization-influenced habitats, including its extremely low taxonomic diversity [10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation